#TITLE_ALTERNATIVE# - AL FARISI PANJAITAN ( NIM : 15108002 ), SALMAN
Fixed point of reference, are urgently needed in a variety of mapping and engineering survey work, as the benchmark reference altitude. But with the land subsidence events that often occur in big cities like Jakarta, the fixed points are also decreased and it does not represent the value of height. Thus, the necessary point of reference remains stable high against the land subsidence events. Based on the observations of experts, land subsidence is caused by taking excess of water in wells, building loads, land compaction, and tectonics. The land subsidence took place between the surface layer and the soil layer where groundwater aquifers are located. This research method did static GPS observations at fixed points which have been started by a particular foundation, GPS observations at least two years as the point of stability testing. The data were processed using Bernese 5.0 scientific software, then the high value of the fixed point processing results observed changes. Height changes that occur at points that are built on the foundation reaches a depth of 400 meters below the ground surface, is not significant, only the millimeter level, and the change is in the interval correction of GPS observations. Thus, these points can be declared stable and fit for use as a fixed point high references in Jakarta.